KERJASAMA INDONESIA DALAM MELAKUKAN IMPOR KAPAS DARI AMERIKA SERIKAT PADA TAHUN 2017-2020 - ", Erika; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study analyses Indonesia's cooperation in importing cotton from the United States in 2017-2020. Indonesia cooperates with the United States in Cotton Imports where the United States is the main destination country to meet Indonesia's domestic Cotton Demand. This study uses a liberalism perspective where international relations are more cooperative than conflictual and the government plays a role in managing the international economy. This study was also analyzed using the theory of International Cooperation. The method used is descriptive qualitative method. This data collection uses literature studies and various literatures that refer to books, journals, theses and websites on the Internet.This study shows the results of Indonesia's cooperation with the United States in 2017-2020. Indonesia's cooperation in Importing Cotton from the United States provides Indonesia with the opportunity to meet the large demand for cotton in the country, where the value of cotton imports by Indonesia from the United States was in 2017 as much as 289.050,000/kg, in 2018 it was 339,012,000/kg, in 2019 as many as 243,404,000/kg and in 2020 as many as 295,307,000/kg.The cooperation carried out by Indonesia and the United States Was first based on an approach, then continued with negotiations/discussion processes and after all of this was carried out, an agreement was created to establish cooperation between the two countries.Â keywords: International cooperation theory, Import of cotton, Liberalism, demand for supply.